2018
DOI: 10.1186/s12864-018-4790-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics reveals the molecular processes of light-induced rapid darkening of the non-obligate cave dweller Oreolalax rhodostigmatus (Megophryidae, Anura) and their genetic basis of pigmentation strategy

Abstract: BackgroundVertebrates use different pigmentation strategies to adapt to various environments. A large amount of research has been done on disclosing the mechanisms of pigmentation strategies in vertebrates either under light, or, living in constant darkness. However, less attention has been paid to non-obligate, darkness dwellers. Red-spotted toothed toads Oreolalax rhodostigmatus (Megophryidae; Anura) from the karst mountainous region of southwestern China are non-obligate cave dwellers. Most tadpoles of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…In this study, the mRNA expression of sox 10 , tyr , slc7a11 and tyrp‐1 genes in red tilapia was directly affected by light duration, similar to results obtained in Oreolalax rhodostigmatus (Zhu et al, ). In the ventral skin of Malaysian red tilapia, sox 10 mRNA expression level was increased in prolonged darkness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the mRNA expression of sox 10 , tyr , slc7a11 and tyrp‐1 genes in red tilapia was directly affected by light duration, similar to results obtained in Oreolalax rhodostigmatus (Zhu et al, ). In the ventral skin of Malaysian red tilapia, sox 10 mRNA expression level was increased in prolonged darkness.…”
Section: Discussionsupporting
confidence: 89%
“…The colour phenotype of different organisms is influenced by the interaction between environmental factors and genetics (Hubbard, Uy, Hauber, Hoekstra, & Safran, ). Among the environmental factors, light condition is known to play a major role in pigmentation by affecting melanin concentration and distribution (Pavlidis, Karkana, Fanouraki, & Papandroulakis, ; Zhu et al, ). Two major types of melanin are known, the eumelanin (black/brown) and pheomelanin (red/yellow) (Bar, Kaddar, Velan, & David, ), which are the important determinants of colour variations in animals (Morgan, Lo, & Fisher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA of each liver or tail sample (n = 3 for each stage or treatment group) was extracted using a TRIzol kit (Invitrogen, Carlsbad, CA, USA), following manufacturer instructions. After RNA quantification, quality assessment and purification, cDNA libraries were built following the methods described by Zhu et al [34]. After cluster generation, the libraries were sequenced on an Illumina HiSeq 2500 platform by Annoroad (Beijing, China), and paired-end reads were generated.…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…Thus, a series of typical phenotypes of cave adaptation in the toad tadpoles, such as small eyes, transparent bodies, and a long developmental cycle [17,18], might be derived from gene loss, pseudogenization or deletion [21], other than fast evolving or positive selection. For example, in O. rhodostigmatus tadpoles, in-frame deletion of four amino acids in the M/EJTD of MC1R supporting the transparent phenotype of the tadpoles [59], was not detected by our fast evolving and positively selective analyses. This indicated that further work on cave adaptation should focus on explorations of gene structure, multiple copy gene families, genomic architecture, etc.…”
Section: Explanations On Genetic Adaptation Of the Cave Species O Rhmentioning
confidence: 60%